A thematic review on digital financial literacy: an emerging concept post covid-19 - Mat Rahim, Nurhazrina; Ali, Norli; Adnan, Mohd Fairuz; Yanto, Heri; Kiswanto (GADING Journal for the Social Sciences, 2024)
Since the outbreak of Coronavirus Disease in 2019 (COVID-19), financial issues have become increasingly challenging due to the growth of digital financial products and services (DFS). Consequently, digital financial literacy (DFL), financially literate from a digital standpoint, is critical for consumers. Despite the increasing number of publications on DFL, the research that comprehensively discusses DFL and the way forward is still insufficient. Therefore, this article will review the recent literature on digital financial literacy. The thematic review has been selected as the method of study. A keyword (digital financial literacy) related to the scope of this research has been identified. In the second step, the keywords for studies in Scopus, WoS, and Science Direct were searched, and a total of 26 papers were reviewed. In carrying out a thematic review, five final themes were identified: measurement of DFL, level of DFL, determinants of DFL, DFL and financial behaviour or inclusion as well as DFL and business performance or development. This study provides an overall view of the recent study related to DFL. More importantly, even though DFL integrates financial literacy and digital literacy, this study highlights a significant disparity between the findings of DFL and traditional financial literacy. Future studies should investigate the detrimental effects of DFL on financial behaviour and find additional advantages of DFL besides enhancing business performance.